Genetic structure and chemical diversity in natural populations of Uncaria guianensis (Aubl.) JFGmel. (Rubiaceae) - Honorio, Isabela Cristina G. [UNESP]; Coppede, Juliana S.; Delprete, Piero G.; Costa, Frederico Henrique S.; Telles, Mariana P. C.; Braga, Ramilla S.; Diniz-Filho, Jose Alexandre F.; Correa, Valeria S. C.; Franca, Suzelei C.; Pereira, Ana Maria S.; Bertoni, Bianca Waleria (Public Library Science, 2018)
Uncaria guianensis is native to the Amazon and is used traditionally as an anti-inflammatory. Natural populations of the species have declined markedly in recent times because of strong anthropic pressure brought about by deforestation and indiscriminate collection. The aim of the present study was to assess the genetic and chemical diversity among eight natural populations of U. guianensis located in the Brazilian states of Acre, Amapa and Amazonas. A set of four primer combinations was employed in sequence-related amplified polymorphism (SRAP) amplifications of leaf DNA, and the fragments were analyzed in an LI-COR model 4300 DNA Analyzer. Genetic variability within the populations (81%) was substantially greater than that detected between them (19%). The highest percentage of polymorphic loci (90.21%) and the largest genetic variability were observed in the population located in Mazagao, Amapa. Genetic differentiation between populations was high (F-st = 0.188) and the studied populations formed three distinct genetic groups (K = 3). The population located in Assis Brasil, Acre, presented the highest average content of the mitraphylline (0.60 mg/g dry weight,). However, mitraphylline and isomitraphylline not detected in most individuals in the studied populations, and it is questionable whether they should be considered as chemical markers of the species. The genetic data confirm the urgent need for conservation programs for U. guianensis, and for further studies aimed at ascertaining the genetic basis and heritability of alkaloid accumulation.